A retrospective study of advanced carcinoma of the cervix treated with a hypofractionated radiation therapy protocol at the department of radiation oncology, University of Witwatersrand, Johannesburg, South Africa - Komen, Ahmed Abdi (My University, 2014)
Background: Carcinoma of the cervix is a common cancer among women in developing countries and with the rising HIV environment the burden of cervical cancer might be even greater, stretching the limited resources even further. This retrospective descriptive study evaluates the potential of the hypofractionated departmental protocol for stage 3b carcinoma of the cervix in terms of toxicity, local control, and compares toxicity for HIV negative and positive patients with a mean follow-up of one year. This study also compares the outcome for unilateral to bilateral pelvic sidewall fixed tumours. Methods and Materials Medical records of 104 sequential patients with stage 3b carcinoma of the cervix treated with departmental hypofractionated protocols between 2010/2011 were reviewed. The patients were only sequential after meeting the criterion of being local with a contact telephone number. Patients were treated with two-dimensional standard pelvic portals of external beam radiation therapy of 2.5Gray daily to a total of 40Gray and intracavitary radiotherapy high dose rate of 9Gray weekly to a total of 18Gray. All cases were stratified by HIV status as being HIV positive or negative and by local disease spread as being unilaterally fixed or bilaterally pelvic sidewall fixed tumours. The patient’s treatment duration and vii haemoglobin levels at the start of radiation were also retrieved from her medical records. Outcome was evaluated after six months, using the Papanicolaou smear and clinically, by using the Response Evaluation Criteria In Solid Tumors criteria version 1.1. Toxicity scoring was done by using the Radiation Therapy Oncology Group/Eastern Cooperative Oncology Group criteria. Maximum toxicity information during treatment and follow-up was obtained from patient files. Statistical analysis was done using STATISTICA version 10. The Student’s T-test was used for mean age and toxicity comparison between HIV positive and negative patients. Survival analysis was done using the Kaplan Meier statistical method. Results: The 600 days overall survival and disease free survival were 94.92% and 59.04% respectively. Comparison of unilateral and bilateral pelvic sidewall fixed tumour disease free survival was 63.94% and 48% (p=0.12926) respectively. Seventy one (68.3%) patients were HIV negative while 33 (31.7%) were HIV positive. Human Immunodeficiency Virus positive patients had a mean age of 45.76 years, while the mean age for HIV negative patients were 55.95 years (p=0.000066). There was no statistically significant difference (p=0.49713) in disease free survival between patients completing radiation therapy in ≤24 days (57.03%) versus >24 days (58.76%). There was no statistically significant difference in the outcomes between HIV positive and negative patients for the up to 600 day’s follow-up period. However, haemoglobin levels were prognostic, as the comparison between viii patients with haemoglobin levels of ≤10g/dl and >10g/dl overall survival was 80.05% and 98.81% (p=0.00055), and disease free survival was 0% and 68.57% (p=0.02130) respectively at 470 days. The treatment was well tolerated and there was no difference in toxicity between HIV positive and HIV negative patients. No patient developed acute grade 3-4 skin and genitourinary toxicity. One patient developed acute grade 3 gastrointestinal tract toxicity. Although the follow-up period was rather short to assess late complications, three patients who were HIV negative had late grade 3 skin toxicity, no patient had late genitourinary toxicity and four had late gastrointestinal tract toxicity. Among the four who had late gastrointestinal tract complications, three were HIV negative while one was HIV positive. Conclusion: For this short follow-up study, the departmental hypofractionated protocol has potential and has already reduced long waiting periods for radiotherapy treatment in our department from six months to two to three months. The treatment is tolerable with a comparable outcome as conventional standard fractionation for stage 3b carcinoma of the cervix. However, long follow-up is recommended to ascertain long term outcome and late complications. As other studies have shown, carcinoma of the cervix is seen at an earlier age among HIV positive patients and screening is recommended. Interestingly, haemoglobin levels are prognostic among stage 3b carcinoma of the cervix, in patients treated with hypofractionation.
A dissertation submitted to the Faculty of Health Sciences, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Medicine in Radiation Oncology. May, 2014
Keywords: Carcinoma; Cervix Uteri